Teaching thinking using Philosophical Inquiry in an online discussion platform at CFS, IIUM - Shamsuddin bin Abdullah (Kulliyyah of Education, International Islamic University Malaysia, 2017)
Online discussion platform serves as an alternative to face-to-face learning. Previous studies indicated that learning can happen through online discussion and there are pedagogies of teaching thinking implemented in an e-learning environment which were successfully implemented. However, no studies on the implementation of the Pedagogy of Philosophical Inquiry (PI) in an online discussion platform could be found. This study investigated the implementation of PI in an online discussion platform (iTa'LeEM and Chatstep) whereby twelve students went through seven PI sessions, one face-to-face and the six were done through iTa'LeEM and another twelve students went through a session through Chatstep. The qualitative observational case-study research utilized participant observation, interview and evaluation of students' work to investigate the implementation of PI in an online discussion platform. Results suggested that firstly, the features of PI were re-created with the addition of elements unique to the experience of e-learning. Secondly, the experience of 'Community of Inquiry' (CoI) was experienced by students to a large extent. Thirdly, students' experience of PI was mainly positive. Fourthly, challenges in implementing PI in online discussion platform were compiled for future use. Results suggested that it is practical to implement PI in an online discussion platform.